Impact of factors influencing capital structure: An analysis of the literature on public companies in emerging markets - Ndruru, Fangandrododo; Ananda, Puteri (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Capital structure is an important element in corporate financial management, especially for public companies in emerging markets. This study aims to analyze the factors that influence capital structure with a qualitative approach, using data from the financial statements of companies listed on the Indonesia Stock Exchange. Methods: Through content analysis and synthesis of findings from various sources, this study identifies key themes relating to profitability, firm size, liquidity, and asset structure as determinants in financing decision-making. Findings: The results suggest that firms in emerging markets should consider the balance between debt and equity to maximize value and financial stability. Trade-off and Pecking Order theories become the foundation for understanding how firms can achieve an optimal capital structure. Conclusion: The selection of the proper capital structure affects not only the performance and value of the company but also its competitiveness in a dynamic market. Novelty/Originality of the Article: This study is expected to make a significant contribution to the literature on capital structure and financial management, as well as provide practical recommendations for companies in making better financing decisions.